The German system of corporate governance: Characteristics and changes - Ulrich Jürgens; Joachim Rupp (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
As Germany enters the 21st century, the traditional system of corporate governance, often referred to as “Deutschland AG”, has come under intense pressure to change. This report seeks to analyze the recent dynamics of the system to assess the extent to which they have already led to an erosion of the traditional characteristics. Many of the distinct features of the German system have shown strong resilience despite the pressure for change, while other features seem to have unraveled quickly. The areas in which these changes appeared to have emerged most profoundly and quickly are in the role of banks and in the role of financial markets. Germany is often cited as a classical case of “non-shareholder value orientation”, whose production-oriented, long-term, risk adverse and consensus-driven values have often been contrasted with the “Anglo-Saxon” approach. The forces currently driving the German political economy towards a shareholder-value orientation can be summarized as follows: State measures to deregulate financial markets; pressure of managers of investments funds and pension funds, in particular from the USA; responses to product-market changes and the internationalization of production. These factors have had an input on all three pillars of the traditional German system: 1. The dominant role of the banks in a complex system of cross-shareholding and in company financing; 2. the system of industrial co-determination; 3. the production- centered, company-centered management system. But the developments are still recent and ambiguous. The question is whether these forces will initiate major and permanent change in the operating principles of the German system or whether they will be superseded by the system's traditional logic. Our report explores these issues in a preliminary way at a point of time when it is not possible to provide a definite answer to what these changes portend. – – Mit dem Übergang in das 21. Jahrhundert gerät das traditionelle deutsche System der Corporate Governance – oft als ,,Deutschland AG“ bezeichnet – unter starken Veränderungsdruck. Die vorliegende Untersuchung beschreibt die gegenwärtigen Veränderungstendenzen und analysiert, inwieweit diese bereits zu einer Erosion des traditionellen Systems geführt haben. Einige der Besonderheiten des deutschen Systems haben sich – so wird in der Studie gezeigt – als außerordentlich veränderungsresistent erwiesen, bei anderen Merkmalen zeigt sich ein rascher Auflösungsprozess. Die stärksten Veränderungen sind hinsichtlich der Rolle der Banken sowie der Finanzmärkte zu verzeichnen. Deutschland wird oft als klassischer Fall einer Nicht-Shareholder-Value-Orientierung angeführt, das mit seiner Langfristorientierung und Risikoaversion, seiner Produktionszentriertheit und Konsensorientierung ein Gegenmodell zum angelsächsischen Ansatz darstellt. Die wichtigsten Triebkräfte für Veränderungen des deutschen Modells hin zu einer Shareholder-Value-Orientierung sind zum einen staatliche Maßnahmen zur Deregulierung der Finanzmärkte, Druck von Seiten internationaler Investment- und Pensionsfonds, insbesondere aus den USA, sowie Reaktionen auf die Entwicklungen auf den Produktmärkten und die Globalisierung. Auswirkungen dieses Veränderungsdrucks lassen sich für jede der drei tragenden Säulen des traditionellen deutschen Systems feststellen: 1. die Rolle der Banken im Rahmen eines komplexen Systems der Eigentumsverflechtungen und Unternehmensfinanzierung; 2. das System der Mitbestimmung und 3. die Produktions- und Unternehmenszentrierung des leitenden Managements. Allerdings handelt es sich um recht neue und in ihrer Wirkung kaum abschätzbare Entwicklungen. Die Frage, inwieweit sie zu einem grundlegenden Wandel des deutschen Systems der Corporate Governance führen, muss daher zum gegenwärtigen Zeitpunkt offen bleiben.
Keywords: 300; Corporate Governance; Institutioneller Wandel; Shareholder Value; Deutschland